Meningkatkan Pemahaman Tentang Iman Dengan Metode Ceramah Pada Masyarakat Dusun Mulyorejo Kampung baru - Lu’lu’ul Jannah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
Understanding and deepening about faith is very important for Muslims, especially for people who in their daily lives are in an environment of various religions, where tolerance is rooted in their understanding. So it takes a solid foundation to fortify the faith of the community. In his own research the author chose to use the PAR (Participatory Action Research) method. The results of this study, perform several steps as follows; The first step we take is to prepare the material that we will convey. The second step is that flexible methods and approaches are needed according to the circumstances. This is because there is often a gap between planning and practice in the field. The third step is to evaluate the delivery that has been carried out from beginning to end to the community. This is an effort to find out how far the material has been captured by the community during the delivery of the material